A flexible, planar energy harvesting device for scavenging road side waste mechanical energy via the synergistic piezoelectric response of K0.5Na0.5NbO3-BaTiO3/PVDF composite films. Issue 39 (3rd October 2017) - Vivekananthan, Venkateswaran; Alluri, Nagamalleswara Rao; Purusothaman, Yuvasree; Chandrasekhar, Arunkumar; Kim, Sang-Jae
Abstract : A probe-sonication derived planar, sustainable composite-piezoelectric nanogenerator was developed to harness the waste mechanical energy. Abstract : Flexible, planar composite piezoelectric nanogenerators (C-PNGs) were developed to harness waste mechanical energy using cost-effective composite films (CFs) prepared via a probe-sonication technique. CFs, made up of highly crystalline, randomly oriented lead free piezoelectric nanoparticles (1 − x )K0.5 Na0.5 NbO3 - x BaTiO3, where x = 0.02, 0.04, 0.06, or 0.08 [designated as KNN- x BTO], were impregnated in a polyvinylidene fluoride (PVDF) matrix. The KNN piezoelectric properties were tuned via the substitution of BTO nanoparticles, without altering the orthorhombic phase. A C-PNG device ( x ≈ 0.02) generates a maximum open circuit voltage ≈160 V, and the instantaneous area power density is ≈14 mW m −2 upon a low mechanical force ≈0.4 N. The effects of BTO concentration in the KNN lattice, electrical poling effects, the fixed weight ratio of nanoparticles in the PVDF matrix, switching polarity tests, and load resistance analysis of C-PNG devices were investigated with constant mechanical force. Furthermore, the experimentally demonstrated C-PNG device output is sufficient to drive commercial blue light emitting diodes. The C-PNG device was placed on a road side, and the maximum energy generation and stability under real time harsh conditions, such as vehicle motion (motorcycle and bicycle) and human walking, were tested. C-PNG generates a peak-to-peak output voltage ≈16 V, when motorcycle forward/backward motion acts on it. This result indicates that the C-PNG device is a potential candidate to power road side sensors, speed tachometers, light indicators, etc. on highways.